2007
DOI: 10.1590/s1806-37132007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Influência do sistema de fornecimento de oxigênio na qualidade de vida de pacientes com hipoxemia crônica

Abstract: Objective: To evaluate the health-related quality of life of patients with chronic obstructive pulmonary disease receiving long-term oxygen therapy (LTOT) at home through oxygen cylinders and compare these results with those obtained six months after the transition from oxygen cylinders to oxygen concentrators. Methods: A total of 45 patients were evaluated. Of those, 24 had chronic hypoxemia and 21 presented no evidence of hypoxemia. The patients with chronic hypoxemia had been regularly receiving LTOT for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
9
0
18
Order By: Relevance
“…LTOT improves mortality in COPD patients with respiratory failure but there appears to be no effect in the less severe patients 177,178,180. There are also positive effects on quality of life73,181 but no proven effect on COPD exacerbations. The relationship with improved quality of life may lead to speculation that this may in part be due to decreased exacerbation rates but most of these studies did not include exacerbation rates as an outcome measure and the MRC study found no relationship with rates of hospitalization 178…”
Section: Immunostimulatory Agents and Vaccinesmentioning
confidence: 99%
“…LTOT improves mortality in COPD patients with respiratory failure but there appears to be no effect in the less severe patients 177,178,180. There are also positive effects on quality of life73,181 but no proven effect on COPD exacerbations. The relationship with improved quality of life may lead to speculation that this may in part be due to decreased exacerbation rates but most of these studies did not include exacerbation rates as an outcome measure and the MRC study found no relationship with rates of hospitalization 178…”
Section: Immunostimulatory Agents and Vaccinesmentioning
confidence: 99%
“…Other benefits of treatment include hemodynamic improvement in hematological parameters, increased exercise capacity, improved quality of life, and improved mental state 1–4…”
Section: Introductionmentioning
confidence: 99%
“…Long-term oxygen therapy (LTOT) is a common treatment provided by pulmonologists and other specialties, mainly in the setting of severe COPD, where it improves survival and quality of life [3,4] as well as other parameters. Burn injuries are an infrequent but potentially life-threatening complication of LTOT and are mainly caused by open flames or sparks used when lighting cigarettes or other tobacco products [5,6].…”
mentioning
confidence: 99%